The Effect of Sleeve Gastrectomy on the Improvement of Random Blood Glucose Levels in Obese Diabetic Rats - Putranto, Indra Kusuma Adi; Mughni, Abdul; Boediono, B. Parish (Green Publisher Indonesia, 2025)
This experimental study investigates the impact of sleeve gastrectomy on blood glucose regulation in obese diabetic rats. Obesity and Type 2 diabetes are major health concerns globally, and sleeve gastrectomy has been identified as an effective bariatric surgery for managing these conditions. The study used a randomized control group pretest-posttest design with two groups: one underwent sleeve gastrectomy, and the other served as a control group. The rats' body weight and blood glucose levels were monitored before and after the procedure. The results demonstrated a significant reduction in random blood glucose levels in the group that underwent sleeve gastrectomy compared to the control group, indicating an improvement in glucose metabolism. These findings suggest that sleeve gastrectomy effectively improves blood glucose levels, potentially due to changes in hormonal and metabolic pathways, particularly the enhancement of GLP-1 secretion, which plays a role in insulin sensitivity. The implications of this research highlight the potential of sleeve gastrectomy as a therapeutic intervention for obesity-related Type 2 diabetes. Further studies are recommended to explore the underlying mechanisms and long-term effects of this procedure in humans and its broader applications in metabolic disease management.